Reframing Qur’anic Family Financial Responsibility: A Mubadalah-Based Approach to Marital Conflict Resolution - Achmad Azis Abidin; Ahmad Musyafiq; Nikmah Rochmawati; M. Sihabudin; Hakki Akmal Labib (Civiliza Publishing, 2026)
This article examines Qur’anic family financial responsibility through a Mubadalah approach to marital financial conflict. The study addresses a gap in gender-sensitive Qur’anic scholarship: reciprocity is often discussed normatively, but rarely translated into an operational model for resolving household financial disputes. Using qualitative library research with a normative-conceptual design, the article analyzes Q.S. al-Nisā’ 4:34, Q.S. al-Baqarah 2:233, and Q.S. al-Ṭalāq 65:6–7 through four stages: identifying textual instructions, mapping relational actors, distinguishing legal assignment from ethical value, and deriving conflict-resolution principles. The findings show that Mubadalah does not erase specific legal obligations of nafāqah. Rather, it reorients their implementation toward capacity, protection, fairness, consultation, transparency, and recognition of both paid and unpaid contributions. The article’s novelty lies in operationalizing Mubadalah into a five-stage conflict-resolution model: interest clarification, capacity assessment, rights-and-duty mapping, transparent communication, and collaborative decision-making. This model reframes marital financial conflict from a struggle over authority into a negotiated process aimed at household welfare, proportional responsibility, and the protection of vulnerable family members.